RANCANG BANGUN SISTEM PENGEMBALIAN UANG KERTAS RUPIAH PADA MESIN VENDING BERBASIS ARDUINO UNO - Alifuddin, Moh (Univeristas Muslim Indonesia, 2019)
Some of the vending machines currently did not have refund systems. Purpose of this research is building a control system prototype to refund the banknote IDR money on the vending machines using Arduino Uno. The sensor was used to detect the nominal and authenticity of money is TCS3200. Authenticity and nominal of money are detected based on the money color that entered in the money reader system. The results of money detection from the TCS3200 sensor then process in the Arduino Uno. Nominal of money has detected in this research is IDR. 20,000, IDR. 10,000, IDR. 5,000, IDR. 2,000 and IDR 1,000. The output of this system is controlling the mechanical machine using DC motor to withdraw the banknote IDR money out from the machine. The system will automatically process if the consumer entered the nominal of money is greater than from goods price on the vending machine.